Preparation method and application of chiral gold nano helical structure particle and achiral molecular complex

By combining chiral gold nanohelix structure particles with near-infrared-responsive achiral dye molecules, the reverse transfer of chiral signals is achieved, and the problem of insufficient signal intensity in the ultraviolet region is solved, and significant CD resonance phenomenon and efficient chiral identification are achieved.

CN119549729APending Publication Date: 2025-03-04HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553544.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems of insufficient signal intensity and low extinction cross-section in the chiral electromagnetic chiral transfer mechanism of chiral molecules in the ultraviolet region, making it difficult to effectively achieve chiral identification.

Method used

By combining chiral gold nanohelix structure particles with visible light resonance characteristics with achiral dye molecules that respond to near-infrared region, the reverse transfer of chiral signals from nanoparticles to achiral molecules is achieved, resulting in CD resonance phenomenon.

Benefits of technology

The chiral signal is significantly enhanced, and the anisotropy factor reaches 0.06, surpassing the performance of ordinary chiral molecules, providing a new idea for the development of near-infrared responsive chiral devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549729A_ABST
    Figure CN119549729A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano photonics and chiral materials, and discloses a preparation method of a chiral gold nano helical structure particle and achiral molecule complex, which comprises the following steps: after centrifugally concentrating gold octahedral nanoparticles prepared by a seed growth method, dispersing the gold octahedral nanoparticles into a hexadecyl trimethyl ammonium bromide solution; dropwise adding the gold octahedral nanoparticles into the gold nano helical structure growth solution, standing in a water bath at 30 DEG C for 2 hours, centrifuging to obtain chiral gold nano helical structure particles, and dispersing the gold nano helical structure particles into a CTAB (Cetyltrimethyl Ammonium Bromide) solution; the achiral molecules are dissolved in ultrapure water, ultrasonic mixing is conducted on the achiral molecules and the gold nano spiral structure particle solution, standing is conducted for 10-12 h at the temperature of 4 DEG C, and the gold nano spiral structure particle and achiral molecule complex is obtained. According to the invention, reverse transfer of chirality from nanoparticles to achiral molecules is realized, an unprecedented CD resonance phenomenon is generated, and a brand new thought is provided for development of near-infrared response chiral devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical fields of nanophotonics and chiral materials, and relates to a preparation method and application of chiral gold nano-helical structure particles and non-chiral molecular complexes. Background Art

[0002] In recent years, the electromagnetic chirality transfer mechanism of organic chiral compounds has greatly promoted the innovation of chiral molecular sensing and circularly polarized light detection technology. Although this field has broad prospects, the limited electronic circular dichroism (CD) signal intensity and low extinction cross section of traditional chiral molecules in the ultraviolet region often become the technical bottleneck of chiral identification. In order to break through this limitation, researchers turned their attention to plasmon technology, using its unique extreme field confinement and light energy enhancement effect to successfully transfer the chiral characteristics from the molecular level to the visible light region plasmon resonance band of non-chiral metal nanostructures, realizing the so-called plasmon-coupled CD, and its signal intensity has achieved a significant order of magnitude jump.

[0003] It is generally believed that this chiral transfer mainly relies on near-field electromagnetic coupling mediated by Coulomb (including dipole and multipole) interactions, or is achieved through far-field coupling of radiation interactions. However, previous studies have focused on the unidirectional transfer of chiral signals from chiral molecules to achiral plasma nanostructures, while the reverse CD transfer induced by chiral plasma nanostructures, that is, the transfer of chiral signals from chiral gold nanoparticles to achiral gold nanoparticles, inducing achiral molecules to produce chiral signals, is theoretically feasible, but has rarely been explored in depth. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a method for preparing a complex of chiral gold nanohelical structure particles and achiral molecules. By combining chiral gold nanohelical particles with visible light resonance characteristics with achiral dye molecules that respond to the near-infrared region (such as indocyanine green, etc.), the reverse transfer of chirality from nanoparticles to achiral molecules is achieved, resulting in an unprecedented CD resonance phenomenon, which provides a new idea for the development of near-infrared responsive chiral devices.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a chiral gold nanohelical structure particle and a non-chiral molecular complex, comprising the following steps:

[0007] 1) centrifugally concentrating the gold octahedral nanoparticles prepared by the seed growth method, and then dispersing them into a hexadecyltrimethylammonium bromide solution;

[0008] 2) adding the gold octahedral nanoparticle solution obtained in step 1) dropwise into the gold nanohelical structure growth solution, standing in a 30° C. water bath for 2 h, centrifuging to obtain chiral gold nanohelical structure particles, and then dispersing the gold nanohelical structure particles into a CTAB solution;

[0009] 3) Preparation of the complex: dissolving the achiral molecule in ultrapure water, and then ultrasonically mixing it with the gold nanohelical structure particle solution obtained in step 2), and then standing at 4° C. for 10 to 12 hours to obtain a complex of gold nanohelical structure particles and achiral molecules.

[0010] The achiral molecules in the above technical solution of the present invention are achiral near-infrared dye molecules.

[0011] The achiral molecule in the above technical solution of the present invention is selected from indocyanine green, IR783 or new indocyanine green.

[0012] The steps for preparing the gold nanohelical structure growth solution in the above technical scheme of the present invention are as follows: prepare 800 μL of 100 mM / L CTAB solution, add it to 3.95 mL of ultrapure water, mix well, and then add 200 μL of 10 mM / L chloroauric acid solution, 475 μL of 100 mM / L ascorbic acid solution, and 5 μL of 5 mM / L L-glutathione solution in sequence.

[0013] In a second aspect, the present invention provides the use of chiral gold nanohelical structure particles and achiral molecular complexes prepared by the above method in infrared responsive chiral devices.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The present invention adopts a bottom-up wet chemical method to successfully synthesize gold nanohelical particles with significant isotropic chiral response, and its anisotropy factor is as high as 0.06, which provides a strong experimental basis for the study of chiral plasma-induced CD. In addition, these gold nanohelical particles show unique CD resonance bands in the visible light range, and their anisotropy factor far exceeds that of ordinary chiral molecules, indicating a significant enhancement of chiral properties at the nanoscale.

[0016] The present invention combines these chiral gold nanohelical particles with visible light resonance characteristics with non-chiral dye molecules (such as indocyanine green, etc.) that respond to the near-infrared region, achieving the reverse transfer of chirality from nanoparticles to non-chiral molecules, producing an unprecedented CD resonance phenomenon. This discovery not only broadens the path of optical chirality induction, but also provides a new idea for the development of near-infrared responsive chiral devices, especially in the current situation where the choice of chiral materials in the near-infrared region is limited, and its potential application value is particularly significant.

[0017] The idea of ​​realizing the reverse transfer of chirality from nanoparticles to achiral molecules in the present invention not only opens up a new direction for the research of chiral plasma-induced CD, but also lays a foundation for the design and application of future optical chiral materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the absorption spectrum of the gold octahedral nanoparticles in Example 1.

[0019] Figure 2 This is the SEM image of the gold octahedral nanoparticles in Example 1.

[0020] Figure 3 This is the absorption spectrum of the chiral gold nanohelical structure particles in Example 1.

[0021] Figure 4 This is the CD spectrum of the chiral gold nanohelical structure particles in Example 1.

[0022] Figure 5 This is the g-factor spectrum of the chiral gold nanohelical structure particles in Example 1.

[0023] Figure 6 This is the SEM image of the chiral gold nanohelical structure particles in Example 1.

[0024] Figure 7 This is the absorption spectrum of the chiral gold nanohelical structure particle-indocyanine green complex in Example 2.

[0025] Figure 8 1 and 2. These are infrared spectra of the chiral gold nanohelical structure particles, indocyanine green, and the chiral gold nanohelical structure particles-indocyanine green complex in Example 2.

[0026] Fig. 9 1 is the SEM-EDS element distribution diagram of the chiral gold nanohelical structure particles and the chiral gold nanohelical structure particles-indocyanine green complex in Example 2.

[0027] Fig.10 This is the CD spectrum of the chiral gold nanohelical structure particle-indocyanine green complex in Example 2.

[0028] Fig.11 This is the absorption spectrum of the chiral gold nanohelical structure particle-IR783 complex in Example 3.

[0029] Fig.12 This is the CD spectrum of the chiral gold nanohelical structure particle-IR783 complex in Example 3.

[0030] Fig.13 This is the absorption spectrum of the chiral gold nanohelical structure particle-IR820 complex in Example 4.

[0031] Fig.14 This is the CD spectrum of the chiral gold nanohelical structure particle-IR820 complex in Example 4. DETAILED DESCRIPTION

[0032] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.

[0033] All glassware was soaked in aqua regia overnight, washed with ultrapure water, and dried for later use. The water used in the experiment was 18.2MΩ ultrapure water.

[0034] The following experimental operations for preparing gold nanohelices were all carried out in a 30°C water bath environment, the complex was refrigerated and kept at 4°C, and care was taken to avoid light during the preparation of indocyanine green solution, IR783 solution, IR820 solution and subsequent related experiments.

[0035] Example 1 Preparation of gold nanohelical structure particles

[0036] 1. Preparation of gold octahedral nanoparticle seed solution

[0037] Prepare 0.32g of hexadecyltrimethylammonium chloride (CTAC), add 9.75mL of ultrapure water, place in a 30℃ water bath and stir to dissolve, add 250μL of 10mM / L chloroauric acid (HAuCl4) and 450μL of 20mM / L sodium borohydride (NaBH4) solution to the solution, stir for 1-2min, and let stand in a 30℃ water bath for 1h.

[0038] 2. Preparation of gold octahedral nanoparticle growth solution

[0039] The growth solution A and growth solution B are exactly the same solution. The specific preparation process is as follows: prepare 0.32g CTAC, add 9.425mL ultrapure water, put it in a 30℃ water bath and stir to dissolve. After it is completely dissolved, add 250μL HAuCl4 with a concentration of 10mM / L, 50μL potassium iodide (KI) solution with a concentration of 1mM / L, and 220μL ascorbic acid (AA) solution with a concentration of 40mM / L to the solution, and mix well. The color of the solution eventually turns colorless.

[0040] 3. Preparation of gold octahedral nanoparticles

[0041] Add 55 μL of gold octahedral nanoparticle seed solution to the above growth solution A, stir for 5 seconds, then take 55 μL of solution from growth solution A and add it to growth solution B, stir for 10 seconds, and let stand in a 30°C water bath for 15 minutes.

[0042] 4. Preparation of gold nanohelical structure growth solution

[0043] Add 800 μL of 100 mM / L hexadecyltrimethylammonium bromide (CTAB) to 3.95 mL of ultrapure water and mix well. Add 200 μL of 10 mM / L HAuCl4, 475 μL of 100 mM / L ascorbic acid solution, and 5 μL of 5 mM / L L-glutathione solution to the mixed solution in sequence and mix well.

[0044] 5. Preparation of chiral gold nanoparticles with helical structure

[0045] The gold octahedral nanoparticles in step 3) were centrifuged at 8000 rpm for 3 min, concentrated to 1 mL, and dispersed in a CTAB solution with a concentration of 1 mM / L. 50 μL of gold octahedral nanoparticles were added to the gold nanohelical structure growth solution and allowed to stand in a 30°C water bath for 2 h.

[0046] The mixture was centrifuged twice (3000 rpm, 2 min), and the chiral gold nanohelical structure particles after centrifugation were dispersed in a CTAB solution with a concentration of 1 mM / L for further characterization.

[0047] 6. Absorption spectroscopy characterization of gold octahedral nanoparticles and chiral gold nanohelical structure particles

[0048] 1 mL of the gold octahedral nanoparticle sample and the chiral gold nanohelical structure particle sample to be tested were dispersed in ultrapure water for dilution. The diluted samples were ultrasonically dispersed in an ultrasonic cleaner. Then the above samples were placed in a 10 mm × 10 mm cuvette and tested using a UV-Vis-NIR spectrophotometer (Agilent Cary5000). The absorption spectra of the samples to be tested were measured, and their optical properties were studied.

[0049] 7. Circular dichroism spectroscopy characterization of chiral gold nanohelical structure particles

[0050] 1 mL of the chiral gold nanohelical structure particle sample to be tested was placed in a centrifuge tube, diluted with ultrapure water, and evenly dispersed by ultrasonication; the diluted sample was placed in a 1 mm × 10 mm cuvette, and the CD spectrum of the sample to be tested was measured using a circular dichroism spectrometer (Applied Photophysics Ltd-Chirascan V100) with a scanning band of 400 to 1100 nm. The entire test was performed in a nitrogen environment.

[0051] 8. Scanning electron microscopy characterization of gold octahedral nanoparticles and chiral gold nanohelical structure particles

[0052] 1 mL of the gold octahedral nanoparticle sample and the chiral gold nanohelical structure particle sample to be tested were respectively placed in a centrifuge tube, diluted with ultrapure water, and the diluted solution was placed in an ultrasonic cleaner for 5 minutes to make the sample evenly dispersed; then 30 μL of the sample solution was dripped on a clean silicon wafer, and placed in a 60°C oven for drying for 24 hours. The dried sample was placed in a SEM testing system (JEOL-JEOL JSM-7610F Plus) to characterize the morphology.

[0053] Figure 1 This is the absorption spectrum of the gold octahedral nanoparticles in Example 1. Figure 2 This is the SEM image of the gold octahedral nanoparticles in Example 1. Figure 3 This is the absorption spectrum of the chiral gold nanohelical structure particles in Example 2. Figure 4 This is the CD spectrum of the chiral gold nanohelical structure particles in Example 1. Figure 5 This is the g-factor spectrum of the chiral gold nanohelical structure particles in Example 1. Figure 6 This is the SEM image of the chiral gold nanohelical structure particles in Example 1.

[0054] like Figure 1 As shown in the figure, the absorption spectrum of gold octahedral nanoparticles shows a sharp absorption peak at 574nm, without any shoulder interference, and the half-peak width is 70nm. Figure 2 Scanning electron microscope image analysis showed that the gold octahedral nanoparticles were successfully prepared with clear outlines, uniform distribution and consistent size, and their edge size was 56nm.

[0055] like Figure 3 As shown in Figure 2, by introducing chiral molecules, the synthesized chiral gold nanohelical structure particles exhibited a wide absorption band in the range of 500 to 1100 nm, with a characteristic absorption peak located at 870 nm. Figure 4 In the CD spectrum, a negative CD peak is observed at 590nm, a positive CD peak is observed at 740nm, and the anisotropy factor is as high as 0.06 (e.g. Figure 5 ), demonstrating its excellent circular dichroism response. Figure 6 The scanning electron microscope images further confirmed the windmill-shaped surface structure of the chiral gold nanohelical structured particles, with uniform particle size, good dispersion, and an average particle size of about 150nm.

[0056] Example 2 Preparation of GNH-ICG complex

[0057] Prepare indocyanine green solution (prepared and used immediately), take 2 mg of indocyanine green (ICG) and dissolve it in 5 mL of ultrapure water by ultrasonic. Dilute the chiral gold nanohelical structure particle solution prepared in Example 1 and adjust its absorbance to 18. Quantitatively take 100 μL of chiral gold nanohelical structure particle solution, add 10 μL, 50 μL, 150 μL, and 300 μL of indocyanine green solution respectively, and add ultrapure water to the mixed solution to ensure that the final mixed solution volume is 0.4 mL, ultrasonically mix evenly, and then place in a 4°C environment for 10-12 hours.

[0058] Figure 7 The absorption spectrum of the chiral gold nanohelical structure particle-indocyanine green complex in Example 2. It can be seen that when indocyanine green is combined with chiral gold nanohelical structure particles, the light absorption characteristics of the composite system do not change significantly. This is mainly due to the strong absorption capacity of ICG itself in the near-infrared region, and the relatively low content of chiral gold nanohelical structure particles in the complex, which masks its absorption contribution. ICG is a negatively charged tricarbonyl dye with a maximum absorption wavelength of 780nm ( Figure 7 shown).

[0059] Figure 8 The infrared absorption spectra of the chiral gold nanohelical structure particles, indocyanine green and the chiral gold nanohelical structure particles-indocyanine green complex in Example 2. It can be seen that after the two are combined, the characteristic absorption peaks of the chiral gold nanohelical structure and indocyanine green appear on the infrared spectrum of the complex at the same time, and the peak at 1002 cm -1 1309cm -1 The vibration peaks at 1008 cm-1 and 1009 cm-2, respectively, are attributed to the symmetric stretching vibration and antisymmetric stretching vibration of the S=O bond in the sulfonic acid group. -1 1286cm -1 The changes in infrared spectra prove that ICG has successfully bound to the surface of the chiral gold nanohelical structure, and the binding of the two is achieved through the interaction between the sulfonic acid groups in the ICG structure and gold.

[0060] Fig. 9 The SEM-EDS elemental analysis results of the chiral gold nanohelical structure particles and the chiral gold nanohelical structure particles-indocyanine green complex in Example 2. Specifically, Fig. 9 a-9d depicts the morphological characteristics and element distribution of gold nanohelical structure particles, and Fig. 9e-9h shows the corresponding morphology and element distribution of the gold nanohelical structure particle-indocyanine green complex. It can be clearly observed from these images that the S element is evenly distributed on the surface of the gold nanohelical structure particles. It is worth noting that the S element on the surface of the chiral gold nanohelical structure particles originates from the modification of glutathione. Further comparative analysis found that the relative content of the S element in the gold nanohelical structure particle-indocyanine green complex showed an increasing trend compared with the simple chiral gold nanohelical structure particles. This significant change in the relative content of the S element indicates that ICG has successfully bound to the surface of the chiral gold nanohelical structure particles to form a stable composite structure.

[0061] Fig.10 It is the CD spectrum of the chiral gold nanohelical structure particle-indocyanine green complex in Example 2. In the CD spectrum analysis, with the increase of ICG content, the original positive CD peak of the gold nanohelix undergoes significant differentiation, evolving from a single peak at 755nm to a new pattern including a negative CD peak at 884nm and a positive CD peak at 950nm (taking 300ICG as an example), and the new peak becomes more obvious with the increase of ICG concentration, showing a red shift trend, while the CD peak at 590nm moves in the blue shift direction with a decrease in intensity.

[0062] Example 3 Preparation of GNH-IR783 complex

[0063] Prepare 2-[2-[2-chloro-3-[2-[1,3-dihydro-3,3-dimethyl-1-(4-sulfonic acid butyl)-2H-indol-2-ylidene] ethylidene]-1-cyclohexen-1-yl] vinyl]-3,3-dimethyl-1-(4-sulfonic acid butyl)-3H-indole sodium salt (IR783) solution (prepared and used immediately), take 1.9 mg IR783 and ultrasonically dissolve it in 5 mL ultrapure water, dilute the chiral gold nano helical structure particle solution prepared in Example 1, and adjust its absorbance to 8. Quantitatively take 100 μL of chiral gold nano helical structure particle solution, add 50 μL, 100 μL, 200 μL, and 300 μL IR783 solution thereto, respectively, and add ultrapure water to the mixed solution to ensure that the final mixed solution volume is 2 mL, ultrasonically mix evenly, and then place in a 4°C environment for 10-12 hours.

[0064] Fig.11 This is the absorption spectrum of the chiral gold nanohelical structure particle-IR783 complex in Example 3. Fig.12 This is the CD spectrum of the chiral gold nanohelical structure particle-IR783 complex in Example 3.

[0065] Example 4 GNH-IR820 complex

[0066] Prepare a new indocyanine green (IR820) solution (prepared and used immediately), take 2.1 mg of the new indocyanine green and dissolve it in 5 mL of ultrapure water by ultrasonication, dilute the gold nanohelix solution prepared in step (2), and adjust its absorbance to 8. Quantitatively take 100 μL of the chiral gold nanohelix structure particle solution, add 50 μL, 100 μL, 200 μL, and 300 μL of the new indocyanine green solution respectively, and add ultrapure water to the mixed solution to ensure that the final mixed solution volume is 0.4 mL, mix evenly by ultrasonication, and then refrigerate at 4°C for 10-12 hours.

[0067] Fig.13 This is the absorption spectrum of the chiral gold nanohelical structure particle-IR820 complex in Example 4. Fig.14 This is the CD spectrum of the chiral gold nanohelical structure particle-IR820 complex in Example 4.

[0068] from Figure 11-14 It can be seen that for the composite system of chiral gold nanohelical structure particles with IR783 and new indocyanine green (IR820), at the absorption spectrum level, due to the strong absorption characteristics of near-infrared dyes, the absorption characteristics of the composite system are almost equivalent to the dye itself, and no significant changes are observed. Specifically, IR783 exhibits the strongest absorption at 774nm, while the strongest absorption of IR820 is located at 810nm at low concentrations, and shifts to 690nm at high concentrations due to the aggregation effect. In terms of CD spectral response, the changes in the CD peaks of the GNH-IR783 and GNH-IR820 complexes with changes in dye concentration are different from those of the GNH-ICG complex. For the GNH-IR783 system, as the concentration of IR783 increases, the CD peak at 590nm blue-shifts and the intensity weakens, and the CD peak at 755nm also gradually weakens until the CD spectra of the two tend to overlap at high concentrations ( Fig.12 ). In contrast, in the GNH-IR820 system, the CD peak at 590nm continued to blue-shift, while the CD peak at 755nm experienced a change process of first weakening and then strengthening ( Fig.14 ), showing a more complex interaction mechanism.

[0069] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for preparing a complex of chiral gold nanohelical structure particles and non-chiral molecules, characterized in that: The following steps are involved: 1) The gold octahedral nanoparticles prepared by the seed growth method were concentrated by centrifugation and then dispersed into a hexadecyltrimethylammonium bromide solution; 2) adding the gold octahedral nanoparticle solution obtained in step 1) dropwise into the gold nanohelical structure growth solution, standing in a 30°C water bath for 2 h, centrifuging to obtain chiral gold nanohelical structure particles, and then dispersing the gold nanohelical structure particles into a CTAB solution; 3) Preparation of the complex: Dissolve the achiral molecule in ultrapure water, and then ultrasonically mix it with the gold nanohelical structure particle solution obtained in step 2), and then let it stand at 4°C for 10-12 hours to obtain a complex of gold nanohelical structure particles and achiral molecules.

2. The method according to claim 1, characterized in that The achiral molecules are achiral near-infrared dye molecules.

3. The method according to claim 1 or 2, characterized in that: The achiral molecule is selected from indocyanine green, IR783 or new indocyanine green.

4. The method according to claim 1, characterized in that: The steps for preparing the gold nanohelical structure growth solution are as follows: prepare 800 μL of 100 mM / L CTAB solution, add it to 3.95 mL ultrapure water, mix well, and then add 200 μL of 10 mM / L chloroauric acid solution, 475 μL of 100 mM / L ascorbic acid solution, and 5 μL of 5 mM / L L-glutathione solution in sequence.

5. Application of the chiral gold nanohelical structure particles and achiral molecular complexes prepared by the method according to any one of claims 1 to 4 in infrared responsive chiral devices.